Analisis Penyebab Kegagalan Produksi Batu Bata Hasil Mesin Extruder dengan Menggunakan Metode FTA (Fault Tree Analysis) (Studi kasus di Perajin Batu Bata Ngunut, Kabupaten Klaten) - Purwandhito, Pulung Aji; WP, Susatyo Nugroho (Industrial Engineering Online Journal, 2015)
Most of the bricks produced conventionally (handmade), the artisans will not be able to meet demand for bricks that so much, while existing tools have not been able to meet the desired brick by brick producers. In order to meet the market demand, brick producers using extruder machine, but the results are worse, because the number of broken bricks increased from 5% to 40% when baked bricks.This study aims to determine the root cause of the failed product using an extruder machine, and give recommendation root causes of failed products using an extruder machine.The results of the study by the method of Fault Tree Analysis shows that the root cause of the problem increased the number of broken bricks from 5% to 40% is to reduce operating costs, have not found the exact formulation, to be in ekstrude horizontally, cutting the results of an extruder with a wire cutter, using the output displacement hand, misinformed, inexperienced, low prices, weather, no drying machine, want a quick sale, no humidity control, and traditions / customs. For that some of the recommendations given are: 1. designing new engines that are more suitable to the type of soil mixture with TRIZ methods; 2. Learn how to drying bricks that are effective and efficient.